Organic structural spectroscopy - Lambert, Joseph B. (Pearson Prentice Hall, 2011)
"Organic Structural Spectroscopy authoritatively presents the fundamentals of all four principal spectroscopic methods: nuclear magnetic resonance spectroscopy, mass spectrometry, infrared spectroscopy, and ultraviolet-visible spectroscopy."--pub. desc